Managing wine quality. Volume 2, - Reynolds, A. G. (Andrew Gordon) (Woodhead Publishing in food science, technology, and nutrition., 2022)
Managing Wine Quality, Volume 2: Oenology and Wine Quality, Second Edition, brings together authoritative contributions from experts across the world's winemaking regions who cover yeasts, fermentation, enzymes, and stabilization, amongst other topics. A new chapter covers, in detail, extraction technologies and wine quality. Other sections cover the management of wine sensory quality, with new chapters covering the management of fortified wines, of Botrytized wines, and of wines produced from dried grapes. In addition, an updated section on insect taints in wine has been widened to cover all insects. With a focus on recent studies, advanced methods, and a look to future technologies, this fully updated edition is an essential reference for anyone involved in viticulture and oenology who wants to explore new methods, understand different approaches, and refine existing practices.